Demand response in Germany: Technical potential, benefits and regulatory challenges - Jan Stede (Deutsches Institut für Wirtschaftsforschung (DIW), 2016)
An increased flexibility of the electricity demand side through demand response (DR) is an opportunity to support the integration of renewable energies. By optimising the use of the generation, transmission and distribution infrastructure, DR reduces the need for costly investments and contributes to system security. There is a significant technical DR potential for load reduction from industrial production processes in Germany, as well as from cross-cutting technologies in industry and the tertiary sector. The availability of demand response as a system resource depends on the underlying type of demand. Already today energy-intensive industries market significant demand capacity in the German minute reserve. The DR literature reveals that there is a potential of several gigawatts of additional capacity available for at least one hour in Germany. Demand can also cover longer periods, but this often requires investment, for example in storage capacity for intermediate products. To enable the effective use and full remuneration of demand response, further improvements in power market design are discussed: (i) Enabling third parties (referred to as Demand Side Management Companies) to help business customers realise their flexibility potential; (ii) creating robust intraday and balancing prices in auction platforms as reference prices for longer-term contracts to stabilise revenue streams of flexibility providers; (iii) it needs to be further assessed whether additional catalysing instruments are necessary to initiate investment in new business processes or storage capacity.
Keywords: 330